Sintesis Membaca Kritis dan Menulis Argumentatif : Model Pembelajaran Progresif dalam Mata Kuliah Bahasa Indonesia - Yohanis A. Rutu Lengo; Yuni Nursyariah Sumarlin; Amira Fadila Sari; Siti Munawara; Yeremias Bardi; Nurlaela Nur Lija (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the integration of critical reading and argumentative writing skills in Indonesian language courses at Universitas Muhammadiyah Maumere as a strategic effort to strengthen students’ academic literacy. In the digital era, university students are increasingly exposed to fragmented information, superficial reading practices, and non academic language use, which significantly affect their ability to construct logical and well supported academic arguments. This research aims to describe learning practices, identify key challenges, and analyze the implications of integrating critical reading and argumentative writing within higher education contexts. The study employs a qualitative descriptive approach using classroom observations and in-depth interviews with lecturers and students. The findings reveal that students initially experience difficulties in evaluating sources, formulating arguments, and maintaining coherence in academic writing. However, the integration of critical reading activities with structured argumentative writing tasks contributes to improved analytical thinking, clarity of reasoning, and academic language use. The study also highlights the central role of lecturers in scaffolding learning processes and fostering reflective academic practices. The findings imply that integrating critical reading and argumentative writing is essential for developing students’ academic identity and intellectual responsibility, particularly in responding to contemporary challenges in higher education and digital literacy.